(untitled) (Journal of Philosophy Culture and Political Science, 2019)
This article discusses the basic concepts of American dominance in the approach of U.S. researchers. The author has analyzed the new trends in the existing international system, requiring the participation of the United States as the fi nal arbiter in the new world order. Keywords: foreign policy of USA, global leadership, international order, geopolitical strategy